Executive Function, Identity, and Career Decision-Making in College Students - Marilyn Welsh; Sarah Schmitt-Wilson (SAGE Open, 2013)
This study examined the relationship among executive function, identity, and career decision-making as self-reported by 82 college students. Participants were administered measures of executive function, identity status, career decision-making, and an index of verbal intelligence. After controlling for intelligence, self-reported difficulties with the metacognitive component of executive function were related to lower levels of identity achievement and higher levels of moratorium and diffusion. Difficulties with behavioral regulation were associated with higher levels of moratorium and foreclosure. Hierarchical multiple regressions with backward elimination indicated that individual differences in career certainty was best explained by metacognitive control and identity achievement. In contrast, variation in career uncertainty was predicted by verbal intelligence, behavior regulation, and low and high scores on identity achievement and diffusion, respectively. These preliminary results fill a gap in the current literature on career decision-making, suggesting the importance of executive function skills to this milestone process in the lives of emerging adults.